2015
DOI: 10.1159/000381961
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Dental Caries Using Colorimetric Characteristics of Fluorescence Spectrum

Abstract: The feasibility of colorimetric parameters for the discrimination of the stages of dental caries based on a light-induced autofluorescence spectrum at a 405-nm excitation wavelength was investigated. The fluorescence spectra of 4 groups of tooth samples (10 sound, 10 early-stage decay, 14 established decay, and 10 severe decay), which were classified by the International Caries Detection and Assessment System, were experimentally measured in vitro. The carious lesion samples had an additional fluorescence peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These components were inserted into different mathematical functions (f x ) used to quantify the fluorescence signal with a single parameter, upon which a caries scoring system for the scanner prototype could be based. A total of 4 functions were investigated in this study, inspired by functions used in commercially available 2D fluorescence imaging devices [Kühnisch et al, 2006;Thoms, 2006;Chen et al, 2015;Jung et al, 2018], albeit with modifications. These functions and their rationale are described below.…”
Section: Reference Test -Histological Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…These components were inserted into different mathematical functions (f x ) used to quantify the fluorescence signal with a single parameter, upon which a caries scoring system for the scanner prototype could be based. A total of 4 functions were investigated in this study, inspired by functions used in commercially available 2D fluorescence imaging devices [Kühnisch et al, 2006;Thoms, 2006;Chen et al, 2015;Jung et al, 2018], albeit with modifications. These functions and their rationale are described below.…”
Section: Reference Test -Histological Assessmentmentioning
confidence: 99%
“…Since the G fluorescence signal alone has also been shown to be an indicator for the level of demineralization in hard dental tissues [Borisova et al, 2006;Gmür et al, 2006;Pretty, 2006;Chen et al, 2015], f 2 was defined to represent the absolute G fluorescence signal measured at the examination sites.…”
Section: Reference Test -Histological Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 The porphyrin derivatives have previously been held responsible for fluorescence emission in the red spectral region of dental biofilm and caries lesions when excited with 405 nm violet light. 10 The porphyrin concentration is high in Gram-negative oral bacteria, which indicates the observed RF was produced by mature and pathogenic biofilms. Also, previous studies have reported that the intensity of RF increased with the biofilm maturation and its pathogenicity.…”
Section: Introductionmentioning
confidence: 99%